Improving existing water supply systems to enhance water availability and accessibility in rural communities : a case of the Mankweng Cluster, Polokwane Municipality, South Africa - Pikirayi, Innocent (University of Pretoria, 2025)
Thesis (PhD (Development Studies))--University of Pretoria, 2025.